2018
DOI: 10.1007/s00126-017-0781-1
|View full text |Cite
|
Sign up to set email alerts
|

Germanium enrichment in supergene settings: evidence from the Cristal nonsulfide Zn prospect, Bongará district, northern Peru

Abstract: Supergene nonsulfide ores form from the weathering of sulfide mineralization. Given the geochemical affinity of Ge to Si 4+ and Fe 3+ , weathering of Ge-bearing sulfides could potentially lead to Ge enrichments in silicate and Fe-oxy-hydroxide minerals, although bulk rock Ge concentrations in supergene nonsulfide deposits are rarely reported. Here, we present the results of an investigation into Ge concentrations and deportment in the Cristal supergene Zn nonsulfide prospect (Bongará, northern Peru), which fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 53 publications
2
20
0
Order By: Relevance
“…The strong anti-correlation between Zn and Fe (R 2 = −0.96; Figure 9b) in our data support specific studies on trace element incorporation in sphalerite [6,8,51,52], which is suggestive of a direct substitution of divalent cations as Zn 2+ ↔Fe 2+ (Figure 8c). Moreover, Figure 10 shows that the strong negative correlation is observed among (Cd + In + Sn + Sb + Fe + Mn + Cu + Ga + Ge + Ag + Co) and Zn (R 2 = −0.94), which suggests that those trace elements (Cd, In, Sn, Sb, Fe, Mn, Cu, Ga, Ge, Ag and Co) mainly exist in the form of isomorphism in sphalerite that is thought to be involved in the mechanism of their enrichment in sphalerite [4,5,53,54].…”
Section: Trace Element Substitution Mechanismsupporting
confidence: 90%
See 2 more Smart Citations
“…The strong anti-correlation between Zn and Fe (R 2 = −0.96; Figure 9b) in our data support specific studies on trace element incorporation in sphalerite [6,8,51,52], which is suggestive of a direct substitution of divalent cations as Zn 2+ ↔Fe 2+ (Figure 8c). Moreover, Figure 10 shows that the strong negative correlation is observed among (Cd + In + Sn + Sb + Fe + Mn + Cu + Ga + Ge + Ag + Co) and Zn (R 2 = −0.94), which suggests that those trace elements (Cd, In, Sn, Sb, Fe, Mn, Cu, Ga, Ge, Ag and Co) mainly exist in the form of isomorphism in sphalerite that is thought to be involved in the mechanism of their enrichment in sphalerite [4,5,53,54].…”
Section: Trace Element Substitution Mechanismsupporting
confidence: 90%
“…Sphalerite (ZnS), one of the most common sulfide minerals, is the major ore of zinc, and approximately 95% of all primary zinc worldwide is extracted from sphalerite ores. Previous studies have shown that the crystal structure of sphalerite could incorporate a broad variety of elements, with the most significant being Fe, Cd, Ga, Ge and In [1][2][3][4][5][6][7][8], along with the presence of some other elements (e.g., Hg, Ag and Cu) [4][5][6][7][9][10][11]. Several studies have noted that substitution of Zn 2+ by bivalent similar-sized cations (e.g., Pb 2+ , Cd 2+ and Co 2+ ) or by coupled substitution mechanisms, which can be extended to tri-and tetravalent elements (e.g., Sb 3+ , In 3+ and Ge 4+ ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bulk mineralogy of the drillcore samples [35] is characterized by ubiquitous quartz and muscovite. The mineralogy of the sulfide bodies is relatively simple, and mostly consists of disseminated dark-brown and Fe-rich sphalerite [49,53], with lesser amounts of pyrite and galena. The nonsulfide mineral association is quite complex, being represented by a wide suite of supergene minerals: smithsonite, hemimorphite, hydrozincite, chalcophanite, goethite, and greenockite [35].…”
Section: Cristal Prospectmentioning
confidence: 99%
“…A few research papers on the geochemistry of FeO/OH associated with supergene non-sulfide mineralization have been published by Mondillo et al [16][17][18][19][20], Santoro et al [21][22][23], Navarro-Ciurana et al [24], Arfè et al [25,26] and Stavinga et al [27]. In their studies, they report that the FeO/OH are commonly enriched in Zn and Pb with traces of several other elements, such as As, Cd, Co, Cu, Ga, Ge, Hg, In, Mo, Ni, Sb, Sc and V. This enrichment can depend on: (i) the chemistry of the primary deposit, and (ii) the pH, Eh and T properties of the fluids circulating during the formation of the deposit [28].…”
Section: Introductionmentioning
confidence: 99%